Radikalna teologija kot hermenevtika nemogočega - Trebežnik, Luka (Poligrafi, 2022)
The article is dedicated to the contemporary thinker from the field of radical theology – John Caputo. By analysing the central concepts of his work, the conti-nuity of his thought is shown and the innovation of his approaches in postmodern religious thought is highlighted. The article traces his career and reflects on some of the main stages of his writing, focusing in particular on his approach to various theories of hermeneutics and new conceptions of religion. It concludes by pointing to the possibility of future readings and new understandings of Caputo's work.
Keywords: Caputo, John D.; deconstruction; dekonstrukcija; hermeneutics; hermenevtika; Interpretacija (filozofija); postmodern religion; postmoderna religija; radical theology; radikalna teologija; Teologija mrtvega Boga; Verstva